2019
DOI: 10.1038/s41467-019-10222-z
|View full text |Cite|
|
Sign up to set email alerts
|

Airway response to respiratory syncytial virus has incidental antibacterial effects

Abstract: RSV infection is typically associated with secondary bacterial infection. We hypothesise that the local airway immune response to RSV has incidental antibacterial effects. Using coordinated proteomics and metagenomics analysis we simultaneously analysed the microbiota and proteomes of the upper airway and determined direct antibacterial activity in airway secretions of RSV-infected children. Here, we report that the airway abundance of Streptococcus was higher in samples collected at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 47 publications
(45 reference statements)
0
36
0
Order By: Relevance
“…The genes involved in the mediumpurple4 were enriched in the immune pathways and neutrophil degranulation. Neutrophils are granulocytes that comprise innate phagocytic cells packed with granules containing proteins with antibacterial function [42,43]. In this study, we identified proteins belonging to three types of neutrophil granules: primary (azurophilic: ELANE, MPO, PRTN3, BPI), secondary (specific: LTF, DEFA4, DEFA1, DEFA1B), and tertiary (gelatinase: PGLYRP1) granules.…”
Section: Discussionmentioning
confidence: 99%
“…The genes involved in the mediumpurple4 were enriched in the immune pathways and neutrophil degranulation. Neutrophils are granulocytes that comprise innate phagocytic cells packed with granules containing proteins with antibacterial function [42,43]. In this study, we identified proteins belonging to three types of neutrophil granules: primary (azurophilic: ELANE, MPO, PRTN3, BPI), secondary (specific: LTF, DEFA4, DEFA1, DEFA1B), and tertiary (gelatinase: PGLYRP1) granules.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the present results are unable to untangle how host environmental conditions, including bacterial-bacterial interactions at the time of infection, might enhance the survival of certain species. 34 However, our group is currently examining the role of airway microbe-host relations in the development of childhood asthma.…”
Section: Moraxellamentioning
confidence: 99%
“…Moreover, the study of the host gene expression response to RSV infection is usually restricted to specific and very homogeneous cohorts, hampering the interpretation of the results, the impact of the conclusions obtained and their translation into a molecular test that could be used in routine clinical practice. The present meta-analysis shows that RSV infection leads to global changes in the host transcriptome, affecting not only the transcriptomic machinery of the airway infected cells [28], but also the expression of hundreds of genes in blood cells (Table S2). In particular, according to our results, RSV alters the expression of >1,500 genes in the host compared to healthy controls, involving e.g., cell cycle and immune system genes.…”
Section: Discussionmentioning
confidence: 87%
“…It has been shown that neutrophils degranulate into the airway in response to RSV, pointing to a local innate response to the infection. Neutrophils degranulation implies the release of antimicrobial substances that may contribute to the control of commensal bacteria in the upper respiratory tract [28].…”
Section: Discussionmentioning
confidence: 99%